1970
DOI: 10.1111/j.1432-1033.1970.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Acylglucoses of the Corynebacteria and Mycobacteria

Abstract: Acylglucoses have been identified as major components of the soluble lipids of Corynebacterium diphtheriae, Mycobacterium smeginatis and BCG, grown in the presence of glucose. These have been purified and the structures determined. All contain one fatty acid per mole of glucose. Mass spectrometry of the methylated lipids and other methylation studies and periodate oxidation indicate that the fatty acids are estcrified to position 6 of the glucose. The major fatty acid of the acylglucose from C. diphtheriae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The formation of higher homologues containing 3 or 4 molecules of 3-hydroxytetradecanoic acids was also observed. [15]. Occurrence of simple a-branched P-hydroxy acid in material of biological origin does not seem to have been reported.…”
Section: Formation Of 3-acyloxy Fatty Acids During the Acidic Hydrolymentioning
confidence: 94%
“…The formation of higher homologues containing 3 or 4 molecules of 3-hydroxytetradecanoic acids was also observed. [15]. Occurrence of simple a-branched P-hydroxy acid in material of biological origin does not seem to have been reported.…”
Section: Formation Of 3-acyloxy Fatty Acids During the Acidic Hydrolymentioning
confidence: 94%
“…coeliaca by preparative t.1.c. as described previously (Brennan, Lehane & Thomas, 1970). Each showed only glucose and fatty acids on alkaline hydrolysis and their chromatographic properties and fatty acyl to glucose ratios indicated a triacylglucose in N .…”
mentioning
confidence: 66%
“…The other type, trehalose lipids containing corynemycolic acid also carry β-hydroxy-α-branched fatty acid moieties and have been described to occur within the genus Rhodococcus (2, Table 1), carrying 30-56 carbon atoms and within the genus Corynebacterium, carrying 22-36 carbon atoms. They are also described to occur in mycobacteria (Brennan et al, 1970) and found in trehalose lipids of Brevibacterium vitarumen (Lanéelle and Asselineau, 1977), Arthrobacter paraffineus and a Nocardia sp. (Suzuki et al, 1969).…”
Section: Trehalose Lipid Mycolic Acid Estersmentioning
confidence: 99%
“…Complete structures of acylglucoses carrying mycolic acid esters have been elucidated and reported to be produced by isolates belonging to the genera Corynebacterium and Mycobacterium (Brennan et al, 1970) (Table 1), whereas acylglucoses carrying fatty acid esters have been described for Brevibacterium spp. (Okazaki et al, 1969) (Table 2).…”
Section: Trehalose-comprising Glycolipidsmentioning
confidence: 99%